RELIABILITY ASSESSMENT OF BEARING CAPACITY OF LAYERED SOILS USING HIGH DIMENSIONAL MODEL REPRESENTATION (HDMR) - Suska, Michał; Puła, Wojciech (Studia geotechnica et mechanica, 2013)
HDMR (High Dimensional Model Representation) is a relatively new method that is used to form response surface based on results obtained through laboratory experiments or through numerical calculations. So far the method has been used mainly in chemistry, although a few studies conducted in recent years show that it can be considered a useful tool in soil mechanics and foundation engineering. The subject matter of this paper is the application of HDMR method to reliability assessment of bearing capacity of layered soils. Madej’s method, widely recognized and used by Polish engineers, is applied to conduct the calculations. In the analysed case bearing capacity is not expressed by means of an explicit formula. To fit the approximate functions of bearing capacity, its values are calculated on a grid of points equally spread on ranges of variables. Finding the relation between input and output data is conducted by means of assessing each variable’s influence on response’s mean value within a given scope. Approximate functions have been used to calculate reliability indices by means of FORM, SORM and Monte Carlo methods.